2015
DOI: 10.1136/annrheumdis-2015-eular.5454
|View full text |Cite
|
Sign up to set email alerts
|

SAT0260 Prevalence of Metabolic Syndrome in Patients with Ankylosing Spondylitis in Morocco: A Cross-Sectional Study of 103 Cases

Abstract: BackgroundMetabolic syndrome (MetS) is a metabolic disorder whose causes are: central obesity, hyperglycemia, dyslipidemia, and hypertension. In ankylosing spondylitis (AS), the prevalence of MetS appears to be high, suggesting that systemic inflammation and therapeutic used play a role in the development of MetS.ObjectivesThe aim of our study was to determine the prevalence of MS in AS, to identify factors associated with its presence, and to evaluate the influence of treatment used on its occurrence.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There is growing recognition of the relationship between metabolic syndrome and ankylosing spondylitis [77][78][79], with one Morrocon study demonstrating a prevalence of 34% and a male predominance of 67% [80] Another study demonstrated treatment with anti-TNF-𝛼 monoclonal antibody infliximab reversed excess insulin levels in non-diabetic patients [77]. It is possible to postulate that there might be a Ankylosing Spondylitis Pathogenesis and Pathophysiology DOI: http://dx.doi.org/10.5772/intechopen.109164 relationship between androgen excess metabolic syndrome and the development of AS, but this relationship requires more research to establish.…”
Section: Sex Hormonesmentioning
confidence: 99%
“…There is growing recognition of the relationship between metabolic syndrome and ankylosing spondylitis [77][78][79], with one Morrocon study demonstrating a prevalence of 34% and a male predominance of 67% [80] Another study demonstrated treatment with anti-TNF-𝛼 monoclonal antibody infliximab reversed excess insulin levels in non-diabetic patients [77]. It is possible to postulate that there might be a Ankylosing Spondylitis Pathogenesis and Pathophysiology DOI: http://dx.doi.org/10.5772/intechopen.109164 relationship between androgen excess metabolic syndrome and the development of AS, but this relationship requires more research to establish.…”
Section: Sex Hormonesmentioning
confidence: 99%
“…7 There is an association between metabolic syndrome and many inflammatory diseases, Previous studies demonstrated a higher prevalence of MS in patients with Psoriasis 8,9 or ankylosing spondylitis. 10,11 Patients with MS have a higher rate of Crohn's disease-related hospitalization compared to those without MS. 12 The inflammatory cytokine, tumor necrosis factor-alpha (TNF-a) plays an important role in the pathophysiology of these inflammatory disorders and in MS. The central role of TNF-a in inflammation has been demonstrated by the ability of agents that block the action of TNF-a to treat a range of inflammatory conditions, including rheumatoid arthritis, ankylosing spondylitis, inflammatory bowel disease and psoriasis.…”
Section: Introductionmentioning
confidence: 99%